The Neo-Babylonian palace as centre of the world - Da Riva, Rocío (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
In the Mesopotamian tradition, the symbolic aspect of royal ideology finds its expression in monumental architecture. The stability of a public building reflects the solidity of a kingship. In times of crisis, the construction of a building goes beyond a mere architectural project and becomes a challenge and a political statement. A usurper is legitimised when/if he is able to complete the task of constructing or renovating a building; in contrast, many kings are criticised as poor rulers if they cannot found a building, or renovate or complete a construction. Nabonidus, for instance, found fault with his predecessors Kurigalzu I, Esarhaddon, Assurbanipal and Nebuchadnezzar II, identifying them as kings who failed to found a temple – a very serious charge. Nebuchadnezzar was a frequent target, since the long shadow of his fame clearly irritated the rather boastful Nabonidus. In any case, a dilapidated temple or wall is an indication of a land in decline, led by a poor ruler who is not supported by the gods. If the buildings are successful, clearly, the king enjoys their favour.